STUDIES ON THE VARIOUS ALLOMETRIC RELATIONSHIPS IN THE INTERTIDAL GREEN MUSSEL, PERNA VIRIDIS LINNAEUS OF ENNORE ESTUARY, MADRAS - Shafee, M S (Indian Journal of Fisheries, 2011)
Comparatively little attention has been paid to the ecology of the Indiangreen mussel, Perna viridis Linnaeus (= Mytilus viridis Linnaeus) despite itsgood potentiality for fishery all along the Indian coastal and estuarine regions.Ennore estuary, Madras, has a large population of these green mussels. Sincethe mussels play a major role in the functioning of this estuarine ecosystem, thepresent study on the relationships between various parameters of these bivalveswould facilitate future works on secondary productivity.